Implementasi Strategi Promosi dengan Digital Marketing Melalui Media Sosial Instagram pada Program Studi S1 Bisnis Digital UNAIC - Annisa Rahayu Pangesti; Zulfikar Yusya Mubarak; Nuni Wulansari; Atika Mahmudah; Muhammad Fahmi Zulfikar (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2022)
In today's society, the use of social media has become a necessity in everyday life as a communication tool that can help people to connect, share and interact, access news and information both locally and globally. This makes the users of social media platforms such as Instagram continue to increase so that it can provide opportunities for companies and product and service providers to build brand awareness, connect with customers, and reach new customers so that it can become a new strategy in marketing and promotion using digital marketing. This research has the aim of implementing a digital marketing strategy through the Instagram social media platform to provide brand awareness and strengthen digital branding so as to increase the number of new students in the Digital Business Undergraduate Study Program at Al-Irsyad University Cilacap. In researching this topic, the writer used a descriptive qualitative method. The data used are primary data and secondary data obtained through interviews, observation, and documentation as a method of collecting data. The results of the study show that digital marketing strategies through Instagram social media are effective promotional media if they are well designed and implemented, so that promotion through digital marketing is an important thing to do to increase brand awareness and strengthen branding.